Effect of Withania somnifera hydroalcoholic extract and other dietary interventions in improving muscle strength in aging rats - Vandana Panda; Amol Deshmukh; Asawari Hare; Sneha Singh; Lal Hingorani; S. Sudhamani (Journal of Ayurveda and Integrative Medicine, 2021)
Background: Aging leads to loss of skeletal muscle, diminished muscle strength, and decline in physical functions. Objective: This study evaluates Withania somnifera and some dietary interventions to combat muscle weakness in aging rats. Materials and methods: Rats (12–13 months old) corresponding to a human age of 60–65 years were assigned to various groups and given orally a standardized W. somnifera extract (WSE, 500 mg/kg) or a protein cocktail comprising soybean (1.5 g/kg) and quinoa (1 g/kg) or a combination of WSE and the protein cocktail or whey protein (1 g/kg) as a reference standard or only resistance exercise for 60 days. Grip strength and blood glucose levels were monitored weekly. At the end of the treatment, total protein, inflammatory markers (CRP, IL-6 and TNF-α), AMPK, malondialdehyde, glutathione, antioxidant enzymes and apoptotic regulator genes (Bax and Bcl-2) were assayed. The biceps brachii muscle of all animals was subjected to histomorphological study. Results: All treatments successfully attenuated aging-elevated glucose, CRP, IL-6, TNF-α, AMPK, malondialdehyde, and Bax levels. A significant restoration of the aging-depleted total protein levels, glutathione, superoxide dismutase, catalase, and Bcl-2 was noted in the treatment groups. An increase in grip strength and greater biceps mass with all treatments indicated regaining of the frail aging muscle's strength and functionality. The WSE + protein treatment elicited the best results among all treatment groups to optimize muscle strength. Conclusion: All the interventions curbed muscle loss and strengthened the skeletal muscle by reducing inflammation, oxidative stress and apoptosis, and increasing ATP availability to the muscle.